From Sickle to Pen: Women's Education and Everyday Mobility in Rural Pakistan. Issue 2 (1st June 2019) - Mughal, Muhammad A. Z.
Abstract : This article discusses the relationship between women's education and their everyday mobility in the rural areas of Punjab, Pakistan. Based on an ethnographic case study from a village in Southern Punjab, information from semi-structured interviews and observations is used to demonstrate an enhanced access to education has altered women's everyday mobility trends. However, questions regarding women's empowerment remain unresolved. Although some rural women have always been engaged in agricultural activities, there have been limitations on their mobility due to cultural sensitivities. I conclude the nature of social and socio-spatial relationships is being negotiated in some cultural contexts of rural Punjab through the changing facets of women's mobility associated with modern education.